352 LOSS OF PRIMARY CILIA PRECEDES KIDNEY CYST FORMATION IN KIF3A KNOCKOUT MICE. Issue 1 (1st January 2007) - Patel, V.; Cobo, P.; Shao, X.; Igarashi, P.
Abstract : KIF3A is a motor protein that is essential for antegrade intraflagellar transport and the maintenance of primary cilia. We have previously shown that kidney-specific excision of Kif3a mediated by Ksp/Cre transgenic mice leads to renal cyst formation by postnatal day (P)5 (Lin et al, PNAS 2003;100:5286-91). The cyst epithelial cells lack primary cilia, but it is not clear if the loss of cilia precedes cyst formation. To better characterize the time course of the mutant phenotype, we produced Pkhd1/Cre transgenic mice that express Cre recombinase under the control of 4.7 kb of the mouse Pkhd1 (ARPKD) promoter. Pkhd1/Cre mice were crossed with R26R mice that express lacZ after Cre/loxP recombination. X-gal staining of bitransgenic Pkhd1/Cre;R26R progeny at P1 revealed that lacZ was specifically expressed in tubular epithelial cells in the renal collecting ducts, intrahepatic bile ducts, and epididymis. No lacZ expression was observed in embryos at E12.5. Pkhd1/Cre mice were crossed with mice carrying a floxed allele of Kif3a and the R26R reporter gene. Analysis of Pkhd1/Cre; Kif3a flox/− ;R262R progeny at P7 showed that the kidneys were morphologically normal and that lacZ was expressed in noncystic collecting ducts. Antibody staining for acetylated tubulin showed that primary cilia were absent in the lacZ -positive collecting duct cells in the Kif3a mutant mice but were present in control littermates. Kidney cysts were observed in mutant mice at P14 and progressively increased in size and number at P21, P35, and P56. All cysts were derived from the collecting ducts and were lined by lacZ -positive cyst epithelial cells. The cyst epithelial cells lacked primary cilia and showed apical localization of ZO-1 and basolateral localization of aquaporin 3. Staining for PCNA showed that cyst epithelial cells had higher rates of cell proliferation compared with wild-type collecting duct cells. No morphologic abnormalities were detected in the livers of Kif3a mutant mice. In conclusion, the formation of kidney cysts in Kif3a mutant mice is directly due to inactivation of Kif3a, which produces a loss of renal cilia that precedes tubular dilatation. Pkhd1/Cre transgenic mice should be useful for tissue-specific targeting of other ciliary genes in the kidney, liver, and epididymis.